Le rapport annuel de l'UE sur l'agriculture est disponible sur Internet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Le rapport annuel de la Commission européenne pour...